The Effect of Impaired Cerebral Autoregulation on Postoperative Delirium in Neonates and Infants After Corrective Cardiac Surgery: A Study on Modifiable Risk Factors for Delirium - Yordan H. Georgiev; Marcel Methner; Maximilian Iller; Juliane Engel; Jörg Michel; Johannes Nordmeyer; Felix Neunhoeffer (Reviews in Cardiovascular Medicine, 2025)
Background: The risk factors for developing postoperative pediatric delirium (PD) are multifactorial and include underlying conditions, cyanosis, surgery, intensive care stay, analgesia used for sedation, and withdrawal symptoms. Disturbed cerebral autoregulation in children with congenital heart disease (CHD) can lead to hyper- and hypoperfusion states of the central nervous system and is potentially associated with poor neurological outcomes. Our study aimed to investigate whether disturbed cerebral autoregulation postoperatively is associated with the onset of PD in children with CHD. Methods: We conducted a prospective observational study in neonates and infants undergoing corrective surgery for CHD via cardiopulmonary bypass (CPB). Cerebral regional oxygen saturation (rSO2) and mean arterial pressure (MAP) were measured within the first 24 hours after surgery in the pediatric intensive care unit (PICU). The cerebral oximetry index (COx) was calculated from these parameters using ICM+ software. A COx ≥0.4 was considered indicative of impaired autoregulation. Delirium symptoms were assessed using the Sophia Observation of Withdrawal–Pediatric Delirium (SOS-PD) score. Results: Cerebral autoregulation was evaluated postoperatively at the bedside of 49 neonates and infants (22 males, 44.9%, vs. 27 females, 55.1%) between January 2019 and April 2023. The median age of the patients was 134 days (interquartile range (IQR): 49.5–184 days), the median weight was 5.1 kg (IQR: 4.0–6.3 kg), and the monitoring duration was 23.0 hours (IQR: 20–24.5 hours). In total, 27/49 (55%) patients developed postoperative PD during their stay in the PICU. There was no statistically significant difference in the duration of globally impaired autoregulation between the delirious and non-delirious groups (14.5% vs. 13.9%, p = 0.416). No evidence was found supporting the effect of MAP outside the lower and upper limits of autoregulation for the onset of postoperative delirium (p = 0.145 and p = 0.904, respectively). Prolonged mechanical ventilation, longer PICU stay, and higher use of opioids and benzodiazepines were observed in the delirious group. Conclusion: Our findings suggest that impairment of cerebral autoregulation cannot solely explain the higher rate of PD in children undergoing congenital cardiac surgery. Rigorous hemodynamic management may potentially minimize the impact of cerebral hypo- or hyperperfusion states during the postoperative period, preventing their harmful effects. Additional studies with a larger sample size are needed to confirm the hypothesis and current findings.